ANTIHYPERTENSIVE THERAPY EFFECTS ON REGULATORY AND ADAPTIVE STATUS OF PATIENTS WITH FUNCTIONAL CLASS I–II CHRONIC HEART FAILURE - S. G. Kanorskyi; V. G. Tregubov; V. M. Pokrovskyi (Российский кардиологический журнал, 2012)
Aim. To identify the optimal therapeutic strategy in Functional Class (FC) I–II chronic heart failure (CHF), in accordance with the effects of different drug classes on the regulatory and adaptive status (RAS). Material and methods. The study included 200 patients with FC I–II CHF, who were randomised into two groups. The first group included 104 patients (mean age 52,8±1,9 years) who received metoprolol succinate extended-release in the mean daily dose of 87,7±7,6 mg. The second group included 96 patients (mean age 55,0±1,4 years) receiving quinapril in the mean daily dose of 21,0±5,5 mg. At baseline and 6 months later, 24-hour blood pressure monitoring, the cardio-respiratory synchronism test, treadmill test with the VO2 max assessment, echocardiography, and the measurement of the plasma levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) were performed. Results. Both medications improved the parameters of left ventricular (LV) diastolic function. However, only quinapril effectively improved LV structure, geometry, and systolic function. Only in the quinapril group, exercise capacity and stress test VO2 max increased, while the reduction in NT-proBNP levels, together with the improvement in RAS parameters, was more pronounced. Conclusion. Compared to metoprolol succinate, quinapril demonstrated more pronounced positive effects on cardiac structure and function, as well as on RAS parameters, in patients with FC I–II CHF.